2016
DOI: 10.1093/jme/tjw045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Abundance and Diversity of Calliphoridae and Sarcophagidae (Diptera) in Sites With Different Degrees of Human Impact in the Iberá Wetlands (Argentina)

Abstract: The aim of the present study was to explore the diversity and describe the spatial distribution of Calliphoridae and Sarcophagidae along an urbanization gradient in the Iberá Wetlands. The flies were collected at 18 sampling points, three per site. In total, 3,318 flies were collected (3,077 blow flies and 241 flesh flies), distributed in 13 genera and 33 species. Calliphoridae was the most abundant, comprised 92.74% of all adult flies. Chrysomya albiceps (Wiedemann), Cochliomyia macellaria (F.), Chrysomya meg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Although the data from this study would suggest it may be more suitable as bait if the aim was to catch Sarcophagidae and Muscidae. Previous studies [ 43 , 44 , 45 ] reported that squid as bait caught a wide range of Calliphoridae, Sarcophagidae and Muscidae species.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data from this study would suggest it may be more suitable as bait if the aim was to catch Sarcophagidae and Muscidae. Previous studies [ 43 , 44 , 45 ] reported that squid as bait caught a wide range of Calliphoridae, Sarcophagidae and Muscidae species.…”
Section: Discussionmentioning
confidence: 99%
“…In South America, most studies focused in/on anthropization gradients have demonstrated the wide influence of environmental anthropization on flesh fly communities (e.g. Linhares, 1981a, 1981b; Mulieri et al ., 2011; Pinilla Beltran et al ., 2012; Yepes‐Gaurisas et al ., 2013; Dufek et al ., 2016; Souza & Zuben, 2016). However, these studies compared the communities only by considering three well‐defined habitat types: urban, rural and wild.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies have found a strong correlation between sarcophagid species and habitat conditions (Sousa et al ., 2011, 2016) (measured in some cases with a synanthropic index), along a degree of urbanization (Linhares, 1981a; Mulieri et al ., 2011; Yepes‐Gaurisas et al ., 2013; Dufek et al ., 2016; Barbosa et al ., 2017), our evaluation represented a restrictive study focused only on one extreme of the anthropization gradient. This framework allowed the first evaluation of such habitat conditions associated to landscape, microhabitat and seasonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…(), amongst other. In addition, researchers have been investigating the diversity and seasonal dynamics of some saprophagous flies using different types of bait (Mulieri et al ., ; Patitucci et al ., ; Battán‐Horenstein et al ., ; Dufek et al ., ; Olea et al ., ). Differences in the performance of baited traps indicate that the type of decomposing organic matter can affect the assembly of species that are attracted, which could be expected because they may differ in terms of both their nutrient composition and their physical and chemical properties (Hanski, ).…”
Section: Introductionmentioning
confidence: 98%